Functional Bandaging in Children with Idiopathic Toe-Walking - Tuncer, Deniz; AKALAN, NAZİF EKİN; Çalışkan, M. Mine; Temelli, Yener; Yiğit, Pakize (NLM (Medline), 2023)
Background: Idiopathic toe-walking (ITW) is a persistent gait pattern with no known etiology characterized as premature heel rise or no heel contact. We investigated the effects of functional bandaging in children with ITW on heel contact during stance phase and on gait quality. Methods: Nineteen children aged 4 to 16 years with ITW and ten age-matched healthy children were included in the study. Elastic adhesive bandages were applied to children with ITW to assist with dorsiflexion. Before bandaging (T0) and immediately (T1) and 1 week (T2) after initial bandaging, the initial contact, loading response, and midstance subphases of gait were analyzed using light pressure sensors and the Edinburgh Visual Gait Score (EVGS). Ten age-matched children with typical gait participated for comparison in T0. The data were analyzed with Friedman and Wilcoxon signed rank tests for within-group comparisons and Mann-Whitney U tests for between-group comparisons. Results: In T0, for the ITW group, no heel contact was observed during stance. In T1, all of the participants achieved heel contact at initial contact and loading response and 56.8% at midstance. In T2, all of the heels continued contact at initial contact and loading response and 54.3% at midstance. The EVGS significantly improved. The Friedman test showed that there were noteworthy improvements between T0-T1 and T0-T2 in video-based observational gait analysis and EVGSs (P < .001), although no difference was found between T1-T2 in video-based observational gait analysis (P = .913) and EVGSs (P = .450). Conclusions: In children with ITW, dorsiflexion assistive functional bandaging was an effective tool to help achieve heel contact on the ground and improve walking quality for a short period after application. Further studies with longer follow-up and larger sample sizes are required to confirm the long-term therapeutic effects of this promising functional bandaging.